2004
DOI: 10.1098/rspb.2004.2701
|View full text |Cite
|
Sign up to set email alerts
|

Multiple mating and reproductive skew in Trinidadian guppies

Abstract: Male offspring production in promiscuously mating species is typically more skewed than female offspring production. It is therefore advantageous for males to seek as many mating partners as possible. However, given the documented benefits of polyandry we expect females, as well as males, to mate multiply. We tested these ideas using Trinidadian guppies, Poecilia reticulata. Fishes were collected from the wild, housed in groups of 10 males and 10 females and allowed to reproduce freely over a period of three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
2
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 40 publications
(58 reference statements)
1
71
2
1
Order By: Relevance
“…However, the sign (negative) of both relationships is consistent with prior evidence for a resource allocation trade-off between somatic growth and ejaculate investment. For example, previous work has shown that relatively small males have a competitive advantage during both controlled sperm competition trials (Evans et al 2003) and in long term and replicated mating experiments (Becher & Magurran 2004). Negative correlations between somatic growth and ejaculates are common in species in which males exhibit alternative reproductive strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sign (negative) of both relationships is consistent with prior evidence for a resource allocation trade-off between somatic growth and ejaculate investment. For example, previous work has shown that relatively small males have a competitive advantage during both controlled sperm competition trials (Evans et al 2003) and in long term and replicated mating experiments (Becher & Magurran 2004). Negative correlations between somatic growth and ejaculates are common in species in which males exhibit alternative reproductive strategies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Novel partners are usually favoured (Hughes et al 1999). Females often mate with several males during each receptive period (Evans & Magurran 2000) and switch partners between broods (Becher & Magurran 2004;Eakley & Houde 2004). This behaviour enhances both the quality and the quantity of the resultant brood (Evans & Magurran 2000;Ojanguren et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The greater slope of the gradient in male gametophytes suggests a polygamous mating system. In many other organisms, a significant difference in slopes between the sexes on the Bateman gradient has been interpreted as a signal of sexual selection (Levitan, 1998;Becher and Magurran, 2004;Tatarenkov et al, 2008;Anthes et al, 2010).…”
Section: Phenology and Genetic Structurementioning
confidence: 99%